La gestion interculturelle de la classe de FLE au cycle secondaire en Algérie - Dalila Berkani (Multilinguales)
Didactics and language pedagogy, give a great deal of importance to the learning of intercultural and intercultural management at school. This is the case of the Algerian school through the reform which aims to develop, among other skills, intercultural competence.Despite these ambitions, we have noticed, following a survey of teachers of FLE at the level of a wilaya located in the north-west of Algeria (Ain-Northwestern), that most teachers have no clear ideas about the concept of skills Cultural and intercultural competences, although they confirm that the development of intercultural skills is covered by programmes of FLE classes. Following these findings, we wonder in this article on how to teach the French cultural element and the aid that must be made to the teacher of FLE. We assume that such aid will avoid weakening the linguistic element and impoverishing it from its cultural content that complements it. We accept that they will therefore allow the learner to communicate in FLE correctly. Finally, we wonder about how to take care of the intercultural whose birth is caused, among other things, the meeting of the local culture (learners ‘ culture) with the foreign culture in the FLE class, while referring to the Research in language didactics-cultures.It is in this perspective that our study will include two parts : highlighting the main incompatibilities and contradictions that we have just mentioned and enumerating some didactic suggestions that could allow them Mitigate.